The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4322/rca.2103
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional, produção e composição das uvas de Niágara Rosada submetidas à aplicação de composto orgânico

Abstract: PALAVRAS-CHAVEVitis sp. Resíduos orgânicos Nutrição mineral Cobertura plástica KEYWORDS Vitis sp. Organic waste Mineral nutrition Plastic sheetinRESUMO: A aplicação de composto orgânico nas linhas e entrelinhas de videiras pode aumentar a disponibilidade de nutrientes no solo, afetando o estado nutricional das plantas, a produção e a composição das uvas. O trabalho objetivou avaliar o estado nutricional, a produção e a composição das uvas de 'Niágara Rosada' (Vitis labrusca L.) sob cobertura plástica e submeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The total N content in whole leaves collected at full flowering and at change in color of the berries in the 2008/2009 and 2009/2010 crop seasons was not affected by the application of organic compost and urea on the soil surface (Table 1), agreeing with the results obtained by CASALI et al (2015) with 'Niágara Rosada' grapevines in the same region. Based on these results, it may be inferred that even in the soil without fertilization, which had 27.0 g kg -1 of organic matter, considered as medium (26-50 g kg -1 ) (CQFS-RS/SC 2004), there is the release of satisfactory quantities of N derived from the mineralization process.…”
Section: Total Nitrogen Content In the Whole Leafsupporting
confidence: 81%
“…The total N content in whole leaves collected at full flowering and at change in color of the berries in the 2008/2009 and 2009/2010 crop seasons was not affected by the application of organic compost and urea on the soil surface (Table 1), agreeing with the results obtained by CASALI et al (2015) with 'Niágara Rosada' grapevines in the same region. Based on these results, it may be inferred that even in the soil without fertilization, which had 27.0 g kg -1 of organic matter, considered as medium (26-50 g kg -1 ) (CQFS-RS/SC 2004), there is the release of satisfactory quantities of N derived from the mineralization process.…”
Section: Total Nitrogen Content In the Whole Leafsupporting
confidence: 81%
“…This fruit yield corresponded to an increase of 3,028 kg ha -1 (31.2%) in relation to control without fertilization and generated the smallest difference in relation to the average yield obtained with plastic cover, of 38.8%. Casali et al (2015) observed quadratic effects of organic compost rates in the number of bunches per plant and in fruit yield, regardless of fertilizer application in 'Niagara Rosada' grapevine. In the present work, the yield of 'Niagara Rosada' fruits without plastic cover was correlated to foliar P (r = 0.51*) and K concentrations (r = 0.60*), unlike that observed in experiment with plastic cover, where such correlations were observed (Table 2).…”
Section: Resultsmentioning
confidence: 82%
“…In contrast, plastic cover increases water availability between lines and decreases it in the superficial layer of planting lines, also decreasing P and K concentrations in limbs and leaf petioles (CHAVARRIA et al, 2009). Although lower decomposition rate of organic compost applied to 'Niagara Rosada' grapevine planting lines with plastic cover in relation to its application between planting lines was expected, there are no interactions between these application sites up to rate of 72 Mg ha -1 in the nutritional status and fruit yield and quality (CASALI et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Lorensini et al (2015) evaluated Cabernet Sauvignon grapevines with annual application of N rates (0,10,15,20,40,80, and 120 kg ha -1 ) and found a quadratic effect for NBP, with the best results obtained with the N rate of 20 kg ha -1 . Casali et al (2015) evaluated the productivity of Niagara Rosada grapevines with increasing bovine manure rates (0, 9, 18, 36, and 72 L plant -1 year -1 ) and also found a quadratic effect for NBP, and the best results were obtained with the use of 9 L manure plant -1 ; higher N rates reduced the NBP, and the authors attributed this result to the excess of N provided by the organic fertilizer.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies on grapevines using increasing N rates (BRUNETTO et al, 2009;LORENSINI et al, 2015), urea and organic fertilizer (BRUNETTO et al, 2013), and increasing rates of OrF (CASALI et al, 2015) found that excessive rates of N or organic materials hinder their production components. It was also observed in the present study; high N rates from urea (90 and 120 kg ha -1 ) or from OrF (approximately 131.0 kg ha -1 ) ( Table 3) generated excess N in the soil, causing significant decreases in the production of the grapevines.…”
Section: Resultsmentioning
confidence: 99%